Love - McAnulty, Stacy; Lew-Vriethoff, Joanne (Philadelphia : Running Press, 2018)
What is love? Can you only express it in fancy meals, greeting cards, and heart-shaped chocolates? Kids will find love everywhere in this delightful book. It can be found in everyday moments such as baking cookies with grandma, notes from Mom in your lunchbox, or a family singing together on a car trip, and it isn't always what you expect! With delightful illustrations by Joanne Lew-Vriethoff and sweetly simple prose by award-winning author Stacy McAnulty, this is the perfect book to teach children what love means, why it's important, and how they can spread the love in their daily lives.
Keywords: Love -- Juvenile literature; Love -- Fiction; Children's stories